„Uz Tita i Partiju“. Djelatnost Antifašističkog fronta žena Bosne i Hercegovine i njihove reakcije na propagandu Informbiroa tokom 1948. i 1949. godine // “With Tito and the Party”. Activity of the women’s Anti-fascist front Bosnia and Herzegovina and their reactions on the Informbiro propanganda during 1948 and 1949 - JASMIN JAJČEVIĆ (Historijski pogledi, 2021)
During the Second World War, the Anti-Fascist Women's Front (AFŽ) was formed in 1942 in Bosanski Petrovac. The outcome of the formation is an attempt at long-term mobilization and organization of women within the Communist Party of Yugoslavia. The women's anti-fascist front was organizationally on the path of anti-fascism and sacrifice in achieving the military, political and other goals of the revolution. At the First Congress of the AFŽ of Yugoslavia, which was held in 1945 in Belgrade, Josip Broz Tito stated the tasks of women, which were crucial for the new state. These were the preservation of brotherhood and unity, the continuation of the fight against the enemies of the new state, preparations for the constitution elections, work on rebuilding the country, enlightening women, humanitarian work with soldiers killed in the war, parents of children killed orphaned and raising children in in the spirit of the People's Liberation Struggle. Also, after the Second World War, the International Democratic Federation of Women was established, which was founded on the initiative of women from the Federation of French Women, and which dealt exclusively with women's issues and issues of interest to women. The women of Yugoslavia, who participated in the congresses in Paris and Budapest, also played a significant role in the establishment and operation of the International Democratic Federation of Women. With the outbreak of open conflict between the countries of Informbiro and Yugoslavia in 1948, and the action of Informbiro's propaganda, it also affected the Bureau of the French Women's Union, which prevented women from Yugoslavia / Bosnia and Herzegovina from attending the 1949 plenary session of the International Democratic Federation of Women in Moscow. This attitude led to women's organizations in cities, villages, peasant labor cooperatives, labor collectives and institutions throughout Bosnia and Herzegovina holding meetings, rallies and conferences, where they openly criticized and protested through letters against the decision and the revocation of calls for women's presence. Of Yugoslavia / Bosnia and Herzegovina at the meeting of the International Democratic Federation of Women in Moscow. The women of Yugoslavia / Bosnia and Herzegovina also had their position after the publication of the Informbiro Resolution on the situation in the CPY in 1948, where they rejected the resolution and sent and expressed their commitment to the CPY and Tito. In this regard, the paper, based on first-rate sources and relevant literature, seeks to present the activities of the Anti-Fascist Women's Front of Bosnia and Herzegovina in the years after World War II, both domestically and internationally (preparation of the International Women's Exhibition, signature collection, with the support of the proposal of the Soviet Alliance on Arms Reduction, etc.), as well as the views on the Informbiro Resolution of 1948 and the reactions of women's organizations in Bosnia and Herzegovina to the Informbiro's propaganda during 1949, due to the impossibility of women's attendance at the International Democratic Federation of Women in Moscow.